Leukocyte-mimicking nanovesicles for effective doxorubicin delivery to treat breast cancer and melanoma. (12th November 2019) - Molinaro, Roberto; Martinez, Jonathan O.; Zinger, Assaf; De Vita, Alessandro; Storci, Gianluca; Arrighetti, Noemi; De Rosa, Enrica; Hartman, Kelly A.; Basu, Nupur; Taghipour, Nima; Corbo, Claudia; Tasciotti, Ennio
Abstract : Biomimetic nanovesicles deriving from leukocytes membrane proteins, called leukosomes, exhibit increased targeting of cancer vasculature and stroma by exploiting the inflammatory pathway responsible for recruiting immune cells to the cancer lesion. Abstract : In the last decades, several approaches were developed to design drug delivery systems to address the multiple biological barriers encountered after administration while safely delivering a payload. In this scenario, bio-inspired and bio-mimetic approaches have emerged as promising solutions to evade the mononuclear phagocytic system while simultaneously negotiating the sequential transport across the various biological barriers. Leukocytes freely circulate in the bloodstream and selectively target the inflamed vasculature in response to injury, infection, and cancer. Recently we have shown the use of biomimetic nanovesicles, called leukosomes, which combine both the physical and biological properties of liposomes and leukocytes, respectively, to selectively deliver drugs to the inflamed vasculature. Here we report the use of leukosomes to target and deliver doxorubicin, a model chemotherapeutic, to tumors in syngeneic murine models of breast cancer and melanoma. Exploiting the inflammatory pathway responsible for recruiting immune cells to the site of injury, leukosomes exhibited increased targeting of cancer vasculature and stroma. Furthermore, delivery of doxorubicin with leukosomes enabled significant tumor growth inhibition compared with free doxorubicin in both breast and melanoma tumors. This study demonstrates the promise of using biomimetic nanovesicles for effective cancer management in solid tumors.